THE ROLE OF SENSITIVE C-FIBERS IN THE DEVELOPMENT OF CARDIOPROTECTIVE EFFECT OF REMOTE ISCHAEMIC PRECONDITIONING - V. Ch. Barsukevich; M. V. Basalay; A. G. Bulgak; A. G. Mrochek (Евразийский Кардиологический Журнал)
To evaluate the role of C-fibers in the development of cardioprotective effect of remote ischaemic preconditioning (RPc) during myocardial ischaemia and reperfusion. Materials and methods: experiments have been conducted on 80 anaesthetized Wistar male rats (250-350g weight), divided into two experimental protocols. Protocol 1. The protocol included 30 neonatal rats, which were divided into two groups. In the first group (n=15), capsaicin was injected to animals in neonatal period in order to degenerate sensitive C-fibers. When achieved 250g, the rats were subjected to 30 min myocardial ischaemia and 120 min reperfusion (Control-AMI, n=7, Capsaicin-AMI, n=6) or 15-min both femoral arteries occlusion 25 min before coronary artery occlusion (Control-RPc, n=8; Capsaicin-RPc, n=9). Protocol 2. The first group of animals (Control) was subjected to 30-min myocardial ischaemia with following 120-min reperfusion only. In the second and third animal group 15-min bilateral femoral arteries occlusion was performed 25 min before the onset (RPc group) or 25 min after the onset (RPc25' group) of ischaemia. The animals of the fourth and fifth groups capsaicin was injected subcutaneously 25 min before the onset and on the 25 min after the onset of ischaemia (Capsaicin and Capsaicin25'groups). Results: Protocol 1. Infarct size was comparable in Control-AMI and Capsaicin-AMI groups (45±4% and 43±1%) respectively. No infarct size reduction was observed in Capsaicin-RPc group compared to Capsaicin-AMI group (p>0,05). Protocol 2. Significant reduction in infarct size was observed in groups, where femoral arteries occlusion was performed 25 min before the onset and on the 25th min after the onset of ischaemia, as well as in those, where capsaicin was injected before myocardial ischaemia, comparing to control group (p0,05 vs. Control). Conclusions: the results suggest that activation of С-fiber afferents by topical application of capsaicin to the peripheral tissue prior to myocardial ischaemia/reperfusion limits myocardial injury, mimicking the effect of remote preconditioning, but it doesn't play a key role in the development of RPc applied 25 min after the onset of ischaemia.